ANALISIS KEMAMPUAN PROBLEM SOLVING PELAJAR (Kasus Pada Pelajar Pendidikan Menengah di yayasan Al-Huda Pekanbaru) - Iskandar, Iskandar (Sekolah Tinggi Ilmu Ekonomi Riau, 2017)
Some students have difficulty identifying the known variables, questions, and strategies for solving the given problem as well. This indicates that students' synthesis analysis ability is still low due to poorly trained. This research type is Class Action Research (PTK) because in this research to overcome the existing problem in class X at Al-Huda Foundation Pekanbaru relates to ability of low student synthesis analysis by applying direct instruction with problem solving method. The results showed that the researcher should be open to all criticisms and suggestions in the effort to improve the quality of physics learning which is indicated by the increase of learning result, the increasing ability of synthesis analysis, and the positive response